The Numerical Semigroup of Phrases' Lengths in a Simple Alphabet - Aureliano M. Robles-Pérez; José Carlos Rosales (The Scientific World Journal)
Let 𝒜 be an alphabet with two elements. Considering a particular class of words (the phrases) over such an alphabet, we connect with the theory of numerical semigroups. We study the properties of the family of numerical semigroups which arise from this starting point.